Is This an Authentic Engineering Activity? Resources for Addressing the Nature of Engineering With Teachers - Pleasants, Jacob (Innovations in Science Teacher Education, 2022)
Including engineering as part of K–12 science instruction has many potential benefits for students, but achieving those benefits depends on having classroom teachers who are well prepared to effectively implement engineering instruction. Science teacher educators, therefore, have an essential role to play in ensuring that engineering is incorporated into science instruction in productive ways. An important component of that work is developing teachers’ understanding of the nature of engineering: what engineering is, what engineers do, and how engineering is both related to yet separate from science. Teachers must understand these concepts to implement engineering design activities that authentically reflect the field. In this article, I describe a sequence of instructional activities designed to help teachers, either preservice or inservice, develop their knowledge of the nature of engineering. At the core of the instructional sequence is a set of stories that provide teachers with descriptions of authentic engineering work. Surrounding the stories are activities that help teachers draw accurate conclusions about the nature of engineering and draw out the implications of those conclusions for instructional decision-making. I provide an overview of the instructional sequence and also share details from my own work with teachers, including transcripts of classroom conversations and the impact of instruction on teachers’ knowledge.